2013
DOI: 10.1037/a0032276
|View full text |Cite
|
Sign up to set email alerts
|

The use of traits and contextual information in free personality descriptions across ethnocultural groups in South Africa.

Abstract: The present study investigates the differences between 3 ethnocultural groups in South Africa in the use of traits and contextual information for personality descriptions and the interaction of these differences with social distance from the target person and with personality domains. Semistructured interviews asking for selfand other-descriptions were conducted with 1,027 Blacks, 84 Coloureds and Indians, and 105 Whites, representing the country's 11 official languages. In Part 1 we found similarities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 65 publications
1
32
0
2
Order By: Relevance
“…With respect to assessment, general factors like the level of abstractness of personality characteristics can affect cross-cultural comparisons (cf. Valchev et al, 2012). When abstractness is a concern, as may often be the case in comparisons between more collectivistic and more individualistic cultures, questionnaire items with specific trait manifestations should be preferred as they have been found to favor structure replicability in more collectivistic groups while not hampering it in more individualistic groups (e.g., Schmitt, Allik, McCrae, & Benet-Martínez, 2007;Schwartz et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to assessment, general factors like the level of abstractness of personality characteristics can affect cross-cultural comparisons (cf. Valchev et al, 2012). When abstractness is a concern, as may often be the case in comparisons between more collectivistic and more individualistic cultures, questionnaire items with specific trait manifestations should be preferred as they have been found to favor structure replicability in more collectivistic groups while not hampering it in more individualistic groups (e.g., Schmitt, Allik, McCrae, & Benet-Martínez, 2007;Schwartz et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…elaborated the most comprehensive list available with these types of sources, which include oral records, print media, literary texts, etc. used literary and academic texts; Cheung et al (1996) used literary texts, proverbs and the spoken language; and and Valchev et al (2013) recorded and transcribed the audio of interviews. , on the other hand, published a book entirely devoted to the automated evaluation of the personality through voice recording and speech analysis, including acoustic measures.…”
Section: The Lexical Approach and The Psychological Study Of Natural mentioning
confidence: 99%
“…It seems plausible that this difference between collectivistic and individualistic cultures manifests as DIF in the endorsement of specific items related to citizenship. This suggestion would be in keeping with conclusions drawn in other cross-cultural studies situated within the South African context, which have also found cultural differences in trait-like personality variables (Valchev et al, 2012;Valchev et al, 2013;Valchev et al, 2014). In the context of this body of research, this serves as sound cause for abductively motivated research into the manner in which such distinctions may be understood using a collectivisticindividualistic theoretical frame.…”
Section: Discussionmentioning
confidence: 56%